Timely Attendance of the First Antenatal Care among Pregnant Women Aged 15–49 Living with HIV in Juba, South Sudan - Angelina Nasira Boi; Jonathan Izudi; Fiona Atim (Advances in Public Health)
Timely attendance of the first antenatal care (ANC) is the period in which pregnant women visit ANC less than four months of pregnancy. There is a paucity of data on timely first ANC attendance and its associated factors among pregnant women living with human immunodeficiency virus (HIV) in Juba. The aim of this study was to investigate timely attendance of the first ANC visit among pregnant women living with HIV. Institutional cross-sectional study was conducted in three public health facilities in Juba by convenience sampling from January 2019 to December 2019. Pearson’s chi-squared test was conducted for bivariate analysis and variables with probability values (p values) less than 5% were considered as statistically significant for multivariable analyses using Fisher’s exact test. At the multivariate level, binary logistic regression analysis was conducted. Out of the 192 participants studied, 27 (14.1%) had timely first ANC attendance as recommended and 165 (85.9%) attended first ANC at four months and above. Distances (adjusted risk ratio [aOR], 7.14; 95% confidence interval [CI], 1.40–36.68), ANC card (aOR, 3.48; 95% CI, 1.17–10.40), waiting time ([aOR], 0.04; 95% CI, 0.01–0.75), and prevention of mother-to-child transmission (PMTCT) services (aOR, 0.12; 95% CI, 0.03–0.56) were the factors associated with timely first ANC attendance. Health education interventions targeting pregnant women attending ANC at health facilities should focus on increasing knowledge and awareness of the importance of timely first ANC attendance.